Leilão reverso para pagamentos por serviços ambientais: uma estratégia para a conservação da natureza - Lobo, Liliane Lopes (Universidade Federal de São Carlos, 2019)
Reverse auctions are recent market mechanisms when designed for environmental conservation purposes, with a view to protecting public property on private land, and with ever increasing foreclosures in various countries. In Brazil, the state of São Paulo is a pioneer making use of auctions for payments for environmental services. In addition to the environmental results, this first contact allows the improvement of the design, as well as the incorporation of reflective practices to the owner regarding the importance and valuation of the services provided, as well as the starting point to understand the processes and results generated. The results of this study refer to the analysis of the first five auctions held, one of them being the pilot, which took place in municipalities located in the São Paulo portion of the Vale do Paraíba, aiming at conservation and restoration actions. Conservation auctions were more attractive, and the average price per hectare was lower in this category, justified by the lower cost of actions of this practice. The vast majority of participants are owners, farmers with livestock as their main activity. When the auction systematics are verified, the existence of rounds reflected in a decrease in the bid value, but they are costly in view of the objective of scale gain. Restoration auctions, albeit with a smaller participation, received bids mostly from landowners with up to four fiscal modules, and characterized as high priority areas for conservation actions, as well as a high supply rate in areas of conservation. permanent preservation.
Reverse auction for payments for environmental services: a strategy for nature conservation
Keywords: Economia ambiental; Políticas públicas; Serviços ecossistêmicos; Environmental economics; Public policy; Environmental services; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA